Design and validation of two scales of sexual communication with the partner in men who have sex with men - Sánchez Medina, Ricardo; Enríquez Negrete, David Javier; Rosales Piña, Consuelo Rubi; Pérez Martínez, Pablo Uriel (Pensando Psicología, 2021)
Aim: Design and validate two scales of sexual communication with the partner in men who have sex with men, which together evaluate five components of communication, content, extension, style, time and context. Methodology: It was divided into two phases, the first to develop the items that make up each scale, and the second to obtain their psychometric properties. 200 men participated in the first phase and 1,190 men participated in the second phase, in both cases with an active sexual life, single and who reported having sex with men, half of them diagnosed with HIV and whose route of infection was through sexual contact. The strategy of modified natural semantic networks was applied to obtain the main ones defined for the stimuli: sexual themes and sexual communication with the partner, based on the results, the items were designed to form two scales. In both phases, the application was carried out in a clinic specialized in the care of people with HIV. Results: The results of the validation show evidence of construct validity and concurrent validity, as well as the internal reliability of each scale showing adequate psychometric properties. Conclusions: It is necessary to evaluate communication considering all its components, for which culturally valid instruments such as the scales presented in this research are required.